KEMAMPUAN MEMBACA DAN KEMAMPUAN BERBICARA SISWA KELAS VIII SMP BUDI AGUNG MEDAN - Maladina Sariyosa (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
The issues raised in this research is the role of literacy in the ability to speak class VIII SMP Budi Agung Medan academic year 2013/2014. While the purpose of this study was to determine a clear picture of the role of literacy in the ability to speak in class VIII SMP Budi Agung Medan 2013/2014 school year. This research is a descriptive study, research subjects were all students of class VIII SMP Budi Agung Medan academic year 2013/2014. The sample in this study were all students of class VIII A SMP Budi Agung Medan totaling 37 students. Data were analyzed by descriptive quantitative. Based on the results of the analysis can be taken, among others: a) The role of literacy in the ability to speak class VIII SMP Budi Agung Medan academic year 2013/2014 as a whole was moderate with an average of 7.5. (B) Orientation reading skills to speech class VIII SMP Budi Agung Medan 2013/2014 academic year, judging from the amount of the sample of 37 students as follows: high-ability students numbered 15 people. Students are capable of being numbered 17 people, and low-ability students amounted to 5 people. The conclusions from the results of this study indicate that the role of reading ability affects the ability to speak class VIII SMP Budi Agung Medan academic year 2013/2014 and can affect students in thinking and develop his talents.